Reading the Fine Print: Ultra-Microstructures of Foraminiferal Calcification Revealed Using Focused Ion Beam Microscopy - Nagai, Yukiko; Uematsu, Katsuyuki; Wani, Ryoji; Toyofuku, Takashi (Frontiers in Marine Science, 2018)
The elemental composition of calcite is of critical value in paleoceanographic reconstructions, yet little is known about biological processes underlying elemental uptake by foraminifers during calcification. Especially crucial in the understanding of elemental composition and distribution is the involvement of organic templates separating different layers of calcite forming the wall of a foraminiferal chamber. In this study, we applied the focused ion beam (FIB) scanning electron microscopy (SEM) technique to the site of calcification (SOC) in a newly growing chamber of Ammonia beccarii, a benthic foraminifer, to reveal the ultra- and microstructure during calcification. This allowed cross-sections of both soft and hard tissues, allowing detailed observation of the SOC across a series of calcification stages. For the first time, we show that numerous voids of calcareous layers and internal organic structures are present within the SOC during the calcification process. The series of SEM observations suggest that organic layers are actively involved in calcite precipitation. We provide the first evidence that the SOC is isolated from surrounding seawater during calcification. Our findings improve the understanding of foraminiferal biomineralization and characterize key conditions under which element partitioning and isotope fractionation occur.